Case Report: Effectiveness of secukinumab in systemic sclerosis with early skin progress after autologous hematopoietic stem cell transplantation and end-stage kidney disease - Strunz, Patrick-Pascal; Labinsky, Hannah; Nagler, Lea-Kristin; Portegys, Jan; Froehlich, Matthias; Gernert, Michael; Schmalzing, Marc (Frontiers in Immunology, 2023)
Autologous hematopoietic stem cell transplantation (aHSCT) represents an effective treatment option in patients with severe forms of systemic sclerosis (SSc) by resetting the immune system. Nevertheless, secondary autoimmune disorders and progressive disease after aHSCT might necessitate renewed immunosuppressive treatments. This is particularly challenging when organ dysfunction, i.e., end-stage kidney failure, is present.In this case report, we present the unique case of a 43-year-old female patient with rapidly progressive diffuse systemic sclerosis who underwent aHSCT despite end-stage renal failure as consequence of SSc-renal crisis. Therefore, conditioning chemotherapy was performed with melphalan instead of cyclophosphamide with no occurrence of severe adverse events during the aplastic period and thereafter. After aHSCT, early disease progression of the skin occurred and was successfully treated with secukinumab.Thereby, to the best of our knowledge, we report the first case of successful aHSCT in a SSc-patient with end-stage kidney failure and also the first successful use of an IL-17 inhibitor to treat early disease progression after aHSCT.